Editorial: A Call for Greater Specification of Core Beliefs - Emanuele Maria Merlo; Liam Alexander MacKenzie Myles; Salvatore Settineri (Mediterranean Journal of Clinical Psychology, 2022)
Recently, there is a growing interest in scientific dissemination. This is due, as highlighted in other contributions (Beck et al., 2019; Loi Di Guardo, 2015; Montesinos, 2008; Settineri Merlo, 2022), to choices made by both university institutions and individual scientists.